SELF EFFICACY DALAM KETERAMPILAN BERBICARA BAHASA INGGRIS MAHASISWA PROGRAM STUDI FILM DAN TELEVISI INSTITUT SENI INDONESIA SURAKARTA - Donie Fadjar Kurniawan; Alya Dhiya Shafa (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2022)
Abstract A Self efficacy is closely related to a person's belief about his ability to produce a certain policy (Bandura, 1999). In this study, self-efficacy is about the beliefs of Film and Television students, ISI Surakarta in speaking English skills. To measure the level of self-efficacy used three devices, namely: magnitude, strength and generality. The method used is qualitative. The research data was collected from informants who are first year students (semester 1 or 2) of the academic year 2021 – 2022 by using purposive sampling finding 18 informants. Data collection techniques are recordings of informants speaking English. The results of this study were eleven informants experienced an increase in speaking time in English. Meanwhile, seven informants did not experience an increase in speaking time.).